2020
DOI: 10.1016/j.asoc.2020.106193
|View full text |Cite
|
Sign up to set email alerts
|

Influence of initialization on the performance of metaheuristic optimizers

Abstract: All metaheuristic optimization algorithms require some initialization, and the initialization for such optimizers is usually carried out randomly. However, initialization can have some significant influence on the performance of such algorithms. This paper presents a systematic comparison of 22 different initialization methods on the convergence and accuracy of five optimizers: differential evolution (DE), particle swarm optimization (PSO), cuckoo search (CS), artificial bee colony (ABC) algorithm and genetic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 55 publications
0
41
0
Order By: Relevance
“…For the differential evolution (DE) algorithm, there are many different variants. After some preliminary experimental studies, in this paper, we will use a simple algorithm with better performance than the original DE, called parameter adaptive DE (DE-a) [49]. The parameters CR and F are chosen in the set r0.5, 0.6, 0.7, 0.8, 0.9s and r0.4, 0.5, 0.6, 0.7, 0.8s, respectively.…”
Section: A Comparison Of Different Initialization Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the differential evolution (DE) algorithm, there are many different variants. After some preliminary experimental studies, in this paper, we will use a simple algorithm with better performance than the original DE, called parameter adaptive DE (DE-a) [49]. The parameters CR and F are chosen in the set r0.5, 0.6, 0.7, 0.8, 0.9s and r0.4, 0.5, 0.6, 0.7, 0.8s, respectively.…”
Section: A Comparison Of Different Initialization Methodsmentioning
confidence: 99%
“…There are two other parameters: population size and the number of iterations. The fact is that DE depends on the number of iterations, a small size of the population can find a better solution after several iterations [49]. Due to the limitations of SDI: the population size cannot be freely chosen.…”
Section: A Comparison Of Different Initialization Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors in [56] carried out a systematic comparison of the effect of 22 different probability distribution initialization methods on the convergence and accuracy of five optimization algorithms. Their results showed that the population size and maximum number of iterations affect most algorithms differently.…”
Section: Related Workmentioning
confidence: 99%
“…Physics-inspired algorithms consist of simulated annealing [13], gravitational search algorithm [14], and quantum computing [15], while sociology-inspired ones usually denote imperialist competitive algorithm [16], brain storm optimization [17], culture algorithm [18], memetic algorithms [19], and so on. More importantly, these MHAs have been widely applied on various practical problems, from engineering [20], [21] to bio-informatics [22], [23], and achieved great successes in comparison with traditional mathematical analysis methods as they can obtain an acceptable solution with reasonable computational burden [24]- [28].…”
Section: Introductionmentioning
confidence: 99%